Study Effects of Pile Shearing to Some Mechanical Properties of Cotton Towel - Giang, Thi Thu Huong; Nguyen, Thu Thuy (Old Journal, 2018)
Pile shearing cotton towel (velvet towel), which is a high-end product being preferred, is being used as household towels and bath towel in hotels, motels, because it has the better water absorption capacity than ordinary towels. This article presents the results of a study to determine that, some of the mechanical properties of 100% cotton shearing towel (shear the pile on one side and on the other without shearing) are different from non-shearing towel. Pile shearing towel has the decreased mass of g/m², the air permeability is almost constant, the tensile strength is not reduced much but the tear strength decreases significantly than the non-shearing towel. In particular, the longitudinal water wicking capacity of the shearing pile towel is higher than the other horizontal direction and much higher than non-shearing towel. This is the scientific basis for determining technological parameters in the weaving process, pile shearing, finishing condition and use process of the velvet towel.